اقتصاديات استخدام الأفران الشمسية في البادية السورية - مسعود صبيح (Tishreen University, 2019)
إن التطور التكنولوجي الذي حدث خلال النصف الثاني من القرن الماضي ويحدث الآن أدى الى زيادة استهلاك الطاقة الى حد لم يكن متوقعاً وباتت مصادر الطاقة التقليدية(الاحفورية والنووية) مهددة بالنضوب، لذلك يجري البحث عن مصادر بديلة للطاقة ولعل أفضلها هي الطاقة الشمسية. إن الفرن الشمسي يعد في مقدمة التطبيقات الأكثر اهتماماً في العصر الحديث في مجال الطاقة الشمسية. شمل هذا البحث على دراسة مرجعية للأفران الشمسية، تسليط الضوء على آلية تطويرها وتحسين أدائها، الدراسة التحليلية والنمذجة الرياضية للفرن الشمسي المستخدم، إعداد برنامج حاسوبي لتحديد السلوك الحراري للفرن الشمسي وتغيرات درجة الحرارة لمحتوياته مع مرور الوقت، أيضاً تحديد التوفير في القدرة الكهربائية بالمقارنة مع حالة استخدام الفرن الكهربائي. إن بيانات المناخ المعتمدة توافق المنطقة التي تم اختيارها لهذه الدراسة ممثلة بالبادية السورية، تقع هذه المنطقة الى الشرق من محافظتي حمص وحماة على بعد 40[Km] الى نهاية الحدود السورية كمناطق ريفية وبادية. الإجراء التجريبي للفرن الشمسي ومراقبة سلوكه الحراري من خلال تسجيل بيانات الحرارة المكتسبة مع الزمن. اجراء مقارنة اقتصادية لمختلف أنواع التكاليف للفرن الشمسي والكهربائي. صياغة الاستنتاجات واستنتاج التوصيات المفيدة للأبحاث المستقبلية. The technological development occurred in the second half of the past century and that we still currently witness served to raise energy consumption to on unexpected levels, and the traditional energy sources (Fusil and nuclear) became at the level of drying up. Therefore, investigations are in progress seeking substitute energy sources, the best form of which may be the solar energy. Sun oven technology applications gained significant attention and concern in modern age in the field of solar energy. This paper covered a reference study for the sun ovens, means of its development and improving its performance, the analytic study and mathematical modeling for the used sun oven, preparing a computer program to determine the thermal behavior for the sun oven and the effects of temperature variation on its contents with passing of time, beside investigating the energy saving and compared with the state of using an electrical oven. The climate data used correspond with region selected for this study is represented in the Syrian Desert. This region is located to the east of Homs and Hamah provinces 40[Kms] to the end of the Syrian border line as rural and desert regions. The experimental procedures of the sun oven and monitoring its thermal behavior through recording the thermal data gained with time has been carried out, carrying on an economic comparison for various costs elements of the sun and electric ovens, then organizing conclusions and drafting recommendations applicable in prospectus research works.